G.G. Rizzo, Il giardino privato di Roberto Burle Marx, Il Sítio. Sessant’anni dalla fondazione. Cent’anni dalla nascita di Roberto Burle Marx, Roma, Gangemi, 2009 - Corsani, Gabriele (Ri-Vista. Research for landscape architecture, 2015)
The Sítio, a garden of 40 hectares, was founded by Roberto Burle Marx in 1949, at Guaratiba (Rio de Janeiro). It is also the center of the friendship between its author and Giulio G. Rizzo. In the book, Giulio Rizzo recalls its birth, the different phases of realization, the scientific and artistic components, the goals, the loving attention of its creator. He also condemns the absurdo actual management that makes it a intact ruin.